2016
DOI: 10.1097/aap.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Regional Versus General Anesthesia and the Incidence of Unplanned Health Care Resource Utilization for Postoperative Pain After Wrist Fracture Surgery

Abstract: Patients who received sBPBs for ambulatory wrist fracture surgery had a higher rate of unplanned health care resource utilization caused by pain after hospital discharge than those undergoing GA. These findings warrant confirmation in a prospective trial and emphasize the need for a defined postdischarge analgesic pathway as well as the potential merits of perineural home catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 21 publications
1
47
1
6
Order By: Relevance
“…The consistent occurrence of strong rebound pain in both groups when the block resolved during the first night was disappointing and a somewhat surprising result of our study, and several authors have discussed this phenomenon . This is in contrast to our previous study during inguinal hernia surgery which showed an excellent and improved analgesia profile for days after block resolution .…”
Section: Discussioncontrasting
confidence: 90%
“…The consistent occurrence of strong rebound pain in both groups when the block resolved during the first night was disappointing and a somewhat surprising result of our study, and several authors have discussed this phenomenon . This is in contrast to our previous study during inguinal hernia surgery which showed an excellent and improved analgesia profile for days after block resolution .…”
Section: Discussioncontrasting
confidence: 90%
“…Participants had less rest pain at two postoperative hours after interscalene block than after shoulder block, but more pain 22 h later, although morphine consumption was similar. Increased pain after a regional block wears off – ‘rebound’ pain – is common, for which most evidence comes from retrospective case series . A similar pattern of delayed but increased pain was described in a randomised controlled trial of brachial plexus blockade vs. general anaesthesia for fixation of distal radius fracture .…”
Section: Discussionmentioning
confidence: 83%
“…2. The self-reported highest pain scores were 5 (3,6) [median(IQR)]in the dexamethasone group and 8 (5,9) [median(IQR)] in the control group respectively (p < 0.001). The patients in dexamethasone group reported highest pain score at 19.7±6.6 h (mean±SD)since block administration while in the control group, the self-reported most severe pain happened at 14.7±4.8 h (mean±SD) after block.…”
Section: Resultsmentioning
confidence: 99%
“…However, rebound pain during nerve block wears off challenges the real bene t of this technique, especially in ambulatory surgery settings [4]. For patients receiving ambulatory surgery, the rebound pain is challenging to prevent or control, especially when it happens at home, which is a common cause of unplanned readmission to hospital [5]. Initially brought out by orthopaedic surgeons, rebound pain after nerve block are gaining more and more attention from anesthesiologists [6][7][8].…”
Section: Introductionmentioning
confidence: 99%